Barakamon 8 - Yoshino, Satsuki; Shipley, Karie; Shipley, Krista (New York, NY : Yen Press, 2015)
"The villagers have nominated handsome young calligrapher Seishuu Handa to compete in the relay race--the main event of their annual sports festival! But while Handa undertakes some super-secret running practice, Hiroshi goes on a job interview, Tama awaits the results of her manga submission, the adults concentrate on defeating Rokunosaki (the neighboring village) and the kids do their best to keep up with the adults!"--Back cover.
"A, all ages"--Back cover.
"First published in Japan in 2014 by Square Enix Co., Ltd."--Colophon.
Book reads from right to left in the traditional Japanese format.
Translated from the Japanese.
3-6.
Keywords: Artists -- Comic books, strips, etc -- Juvenile fiction; Calligraphers -- Comic books, strips, etc -- Juvenile fiction; Country life -- Japan -- Comic books, strips, etc -- Juvenile fiction; Islands -- Comic books, strips, etc -- Juvenile fiction; School children -- Comic books, strips, etc -- Juvenile fiction; Artists -- Fiction; Calligraphers -- Fiction; Country life -- Japan -- Fiction; Islands -- Fiction; Students -- Fiction; Artists -- Comic books, strips, etc -- Fiction; Calligraphers -- Comic books, strips, etc -- Fiction; Country life -- Japan -- Comic books, strips, etc -- Fiction; Islands -- Comic books, strips, etc -- Fiction; Manga; School children -- Comic books, strips, etc -- Fiction; Graphic novels; Humorous comics